A DNA barcode survey of marine macroalgae from Bergen (Norway). Issue 10 (26th November 2019) - Bringloe, Trevor T.; Sjøtun, Kjersti; Saunders, Gary W.
ABSTRACT: Safeguarding the services provided by marine forests inherently depends on an accurate understanding of macroalgal species diversity. Here, we provide the first DNA barcode survey of marine macroalgae from Norway, with a focus on the Bergen area, and compared our findings to morphological listings for the corresponding location. Specimens were sampled 14–20 April and 3–13 June 2016, and variously sequenced for several genetic markers, including the five prime end of the cytochrome c oxidase subunit I gene (COI-5P), elongation factor tufA, and the ribulose-1, 5-biphosphate carboxylase large subunit gene ( rbc L). We generated 655 new barcode records for COI-5P, 11 for tufA, and 50 for rbc L, representing nine species of Chlorophyta, 51 species of Phaeophyceae, and 74 species of Rhodophyta. Sequence data confirmed the presence of 113 morphological species. A further 17 genetic groups indicated the presence of new species for the area, only six of which were linked to formally described species. The remaining four genetic records were uncertain in terms of morphological species assignment and relation to the local flora. We recommend further DNA barcoding surveys in the area, as only a third of the listed morphological species were genetically confirmed.